GEOLOGY AND RESERVOIR MODELLING OF MRB SANDSTONE OF LOWER CIBULAKAN MEMBER, CIBULAKAN FORMATION, INDRAMAYU FIELD, NORTH WEST JAVA BASIN, INDONESIA - Regatha Barus , Mada
Indramayu Field is located at +/-6,47582o LS dan +/-108,31032o BT. Geologically, Indramayu Field is located in North West Java Basin. This field has several anticlines associated with north-south trending normal faults at 2800-2900m depth. Based on cutting description, two formations are found in this field that is Cibulakan Bawah Member and Cibulakan Tengah Member. The geological and reservoir modelling studies are focused in Cibulakan Bawah Formation with a sandstone reservoir which is MRB Sandstone. MRB Reservoir has sandstone lithology with 20-40 meters thick. In this reservoir, there are some intercalated sandstone and claystone in several wells. Based on depth structure map, this reservoir is located at 2800-2900 meters depth. This reservoir predominantly has cylindrical, bellshaped and irregular log characteristics. This field consist of three facies that is meandering channel, floodplain and tidal mudflat. Petrophysics analysis results shows that porosity cut off value is 0.07, vshale cut off value is 0.4 and water saturation cut off value is 0.076. Hydrocarbon type that has been found in this reservoir is gas. Type of hydrocarbon contact is GDT/Gas Down to at 2853 m depth. Estimation of Initial Gas in Place in this field is 51 BSCF.